Introducing earhtworms to generate sustainable microenvironments able to modify soil hydrological properties on vineyards - Carvajal-Pachón José; Cambronero-Ruiz Laura; Serrano-Bernardo Francisco; Zuazo Víctor Hugo Durán; Rodrigo-Comino Jesús (Journal of Hydrology and Hydromechanics)
Water infiltration and other physical soil properties are crucial determinants of soil quality and productivity. While it's established that earthworms can enhance soil structure, there's limited research quantifying their impact on these processes, particularly in vineyards. This study assesses the effect of introducing earthworms (Lumbricus terrestris) into soils under controlled conditions, focusing on improvements in soil infiltration, respiration, aggregate stability, moisture, and other key soil properties within Mediterranean vineyards. The research was conducted from December 2023 to April 2024, utilizing experimental microenvironments designed to mimic the natural conditions of vineyard soils in Granada, Spain. Results demonstrated that earthworm activity significantly increased both infiltration capacity and rate. Notably, infiltration was twice as fast in the treated plots from the third measurement onward. Furthermore, earthworms enhanced organic matter accumulation, with gains exceeding 1%, and boosted soil respiration by over 50 ppm. Although aggregate stability showed less dramatic improvement, the data indicate that earthworm-created galleries foster beneficial microenvironments for soil dynamics. These findings highlight the potential of earthworms as regenerative agents in degraded agricultural soils, emphasizing their capacity to support sustainable agricultural practices and mitigate the effects of climate change. Further long-term research in real-world settings is recommended to validate the scalability of these results.